1991
DOI: 10.1071/rj9910096
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of warren ripping for rabbit control in semi-arid South Australia.

Abstract: Warren ripping and poisoning were used to control rabbits on the flood-out plain of a major creek system on Manunda Station, a sheep-grazing property near Yunta in semi-arid South Australia. Rabbit numbers were initially reduced by >99 per cent, as indicated by the number of active entrances remaining in rabbit warrens. After nearly 10 years without follow-up control work, ripped warrens had only two per cent of the pre-control number of active entrances. Poisoning effectively reduced rabbit numbers in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 10 publications
1
27
2
Order By: Relevance
“…This effect would be exacerbated at larger distances, which would receive fewer dispersers from the source population and would be predominantly male-biased (Myers et al 1994). This was illustrated in studies of warren ripping undertaken in the arid zone in Queensland and South Australia where ripped warrens were not re-established, even when rabbits had ready access to the ripped areas (Mutze 1991;Berman et al 2011). Mutze (1991) suggested that ripping had changed the soil texture such that burrow establishment was no longer suitable for rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This effect would be exacerbated at larger distances, which would receive fewer dispersers from the source population and would be predominantly male-biased (Myers et al 1994). This was illustrated in studies of warren ripping undertaken in the arid zone in Queensland and South Australia where ripped warrens were not re-established, even when rabbits had ready access to the ripped areas (Mutze 1991;Berman et al 2011). Mutze (1991) suggested that ripping had changed the soil texture such that burrow establishment was no longer suitable for rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…This was illustrated in studies of warren ripping undertaken in the arid zone in Queensland and South Australia where ripped warrens were not re-established, even when rabbits had ready access to the ripped areas (Mutze 1991;Berman et al 2011). Mutze (1991) suggested that ripping had changed the soil texture such that burrow establishment was no longer suitable for rabbits. Hence, Berman et al (2011) suggested that ripping of warrens within 1 km of permanent water (a drought refuge for rabbits) would be sufficient to suppress rabbit numbers over a much larger area because rabbits rarely travel further than this in search of water.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations